Memfasilitasi Penerapan Sistem Terpadu di Klinik Estetika D.A.N - Saluky Saluky; Reza Oktiana Akbar; Heru Purnomo Kurniawan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
FACİLİTATİNG THE ADOPTİON OF INTEGRATED SYSTEMS AT D.A.N AESTHETİCS CLİNİC, Assistance in implementing an integrated system in clinics and aesthetic services aims to optimize operational efficiency while enhancing service quality. This study focuses on identifying challenges encountered in adopting an information technology system that combines key functions such as patient management, scheduling, electronic medical records, and inventory management. These challenges often relate to staff adaptation to new technology and the need for adequate technical support. The implementation process includes several methods, such as needs analysis, comprehensive staff training, and regular evaluations to assess system effectiveness. Research findings reveal that intensive and continuous assistance plays a crucial role in the successful adoption of this system. Responsive technical support can help reduce psychological and technical barriers to changes in work systems, ultimately increasing acceptance and user satisfaction. The study shows that with proper assistance, clinics can achieve higher efficiency in their daily operations. The system’s implementation contributes to improved quality in aesthetic services. Supporting the use of an integrated system enables clinics to provide more professional and faster services, resulting in greater patient satisfaction. Thus, assistance not only aids in clinical efficiency but also has a positive impact on patient experience and satisfaction, which are the primary goals of healthcare services.